2020
DOI: 10.33365/tb.v3i2.840
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Factors of Consumer Behavioral Intention Towards Online Food Delivery Services

Abstract: The aims of this study is to investigate what are the influence factors of consumer behavioral intention toward online food delivery services (OFD). 200 valid questionnaires were collected to empirically test the research  model using partial least square (PLS) path modelling approach. The result imply that proposed hypotheses were supported except for the relationship between prior saving orientation and convenience motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…The significance value of the relationship between time saving benefit and customer intention is 0.001, which is less than 0.05, showing a strong influence. Previous research by Yeo et al (2017), Lau and NG (2019), Novita andHusna (2020), andHong et al (2021) also highlight the significance of time saving benefits in consumer attitudes and behavior towards online food delivery services, particularly during the pandemic.…”
Section: Findings Discussion and Conclusionmentioning
confidence: 94%
See 3 more Smart Citations
“…The significance value of the relationship between time saving benefit and customer intention is 0.001, which is less than 0.05, showing a strong influence. Previous research by Yeo et al (2017), Lau and NG (2019), Novita andHusna (2020), andHong et al (2021) also highlight the significance of time saving benefits in consumer attitudes and behavior towards online food delivery services, particularly during the pandemic.…”
Section: Findings Discussion and Conclusionmentioning
confidence: 94%
“…Previous research by Yeo et al . (2017), Lau and NG (2019), Novita and Husna (2020), and Hong et al . (2021) also highlight the significance of time saving benefits in consumer attitudes and behavior towards online food delivery services, particularly during the pandemic.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Relevant studies in social psychology have shown that human behaviours are infuenced by internal beliefs. Whether an individual will carry out a certain behaviour is ultimately determined by the mediating variable of behavioural intention [40,41]. A similar mechanism exists for driver distraction.…”
Section: Infuence Of Demographic Variablesmentioning
confidence: 96%